Analisis Desain Food Pan Steel Menggunakan Software Solidworks 2022 - Rizqon Nur Wahid Maulana; Hadi Wibowo (PT. AHLAL PUBLISHER NUSANTARA, 2026)
This study aims to analyze the design of Food Pan Steel, focusing on predicting material failure under pressure from dies during the production process. Solidworks 2022 software was used as a simulation tool to evaluate deflection and potential material failure modes. The simulation results showed that the initial design, without modification, experienced a displacement of 6.782×10⁻¹ mm, while the design modified with the addition of threaded features showed a smaller displacement of 2.741×10⁻² mm. This significant difference indicates that the design with threads reduces material deformation and improves structural efficiency. In addition to mechanical aspects, the design with threads also offers advantages in terms of safety, cleanliness, and aesthetics. The rounded corners of the design minimize injury risks, facilitate cleaning, and enhance the visual appearance of the product, making it more hygienic and compliant with food industry standards. Overall, this analysis emphasizes that appropriate design engineering plays a crucial role in enhancing the quality, safety, and comfort of using Food Pan Steel in professional kitchen environments. Keywords: Food Pan Steel, Solidworks, displacement, threading, hygienic design, deflection simulation, analysis Abstrak Penelitian ini bertujuan untuk menganalisis desain Food Pan Steel dengan fokus pada prediksi kegagalan material saat mengalami tekanan dari dies selama proses produksi. Untuk itu, digunakan software Solidworks 2022 sebagai alat bantu simulasi guna mengevaluasi defleksi dan potensi mode kegagalan material. Hasil simulasi menunjukkan bahwa desain awal tanpa modifikasi mengalami displacement sebesar 6.782×10⁻¹ mm, sementara desain yang telah dimodifikasi dengan menambahkan fitur filetan menunjukkan displacement lebih kecil, yaitu 2.741×10⁻² mm. Perbedaan signifikan ini menunjukkan bahwa desain dengan filetan mampu mengurangi deformasi material dan meningkatkan efisiensi struktural. Selain aspek mekanis, desain dengan filetan juga memberikan keunggulan dari sisi keamanan, kebersihan, dan estetika. Sudut membulat pada desain meminimalkan risiko cedera, mempermudah pembersihan, serta meningkatkan tampilan visual produk, sehingga lebih higienis dan sesuai dengan standar industri makanan. Keseluruhan analisis ini menegaskan bahwa rekayasa desain yang tepat berperan penting dalam meningkatkan kualitas, keamanan, dan kenyamanan penggunaan Food Pan Steel dalam lingkungan dapur profesional. Kata Kunci: Food Pan Steel, Solidworks, displacement, filetan, desain higienis, simulasi defleksi, analisis